Pre‐diabetes in adults 45 years and over in Ireland: the Survey of Lifestyle, Attitudes and Nutrition in Ireland 2007. Issue 10 (12th June 2013) - Buckley, C. M.; Madden, J.; Balanda, K.; Barron, S.; Fahy, L.; Harrington, J.; Perry, I. J.; M. Kearney, P.
Abstract Objectives Pre‐diabetes is an important indicator of future diabetes burden and many countries are reporting prevalence estimates of pre‐diabetes. To date in Ireland, estimates of the prevalence of pre‐diabetes were unavailable. Our objectives were to estimate the prevalence of pre‐diabetes in a nationally representative sample of Irish adults and to explore determinants of pre‐diabetes. Methods The Survey of Lifestyle Attitudes and Nutrition 2007 was a cross‐sectional survey on health and lifestyle in a nationally representative sample of Irish adults. Analysis was performed on a subsample of 1132 participants ≥ 45 years who provided blood samples. Determination of pre‐diabetes was based on American Diabetes Association HbA1c cut points of 39–46 mmol/mol (5.7–6.4%). To explore determinants, we modelled pre‐diabetes prevalence as a function of a set of health system and socio‐demographic variables using logistic regression. Results The overall weighted prevalence estimate of pre‐diabetes in participants ≥ 45 years was 19.8% (95% CI 16.4–23.9). There was no significant difference between age or gender‐specific prevalence rates. Obesity was significantly associated with pre‐diabetes on univariate and multivariate analysis. Population attributable fraction estimates for excess BMI, physical inactivity and poor diet as causes of pre‐diabetes were 31.3% (95% CI –3.9 to 54.5), 10.0% (95% CI –2.7 to 21.3) and 6.1% (95% CI –4.9 to 15.9), respectively. Conclusions The high levels of pre‐diabetes detected in this study are worrying. Population level interventions to address diet and lifestyle factors are needed urgently to prevent progression to diabetes in high‐risk individuals.